Stability of Routine Hematology Sample Using The Medonic M-Series Analyzer - Maharani, Eva Ayu; Astuti, Dewi (Medical Laboratory Technology Journal, 2020)
Routine hematology tests (Hb, Hct, RBC, WBC, PLT) generally done by automation methods using a hematology analyzer. Ideally, the examinations should be done as soon as possible, although, in some circumstances, it can be delayed. Based on the literature, the sample for routine hematology testing should be processed within 4 – 8 hours of venesection. Some studies revealed that the sample could be stored for up to 48 hours, and it can be influenced by the technology applied to the hematology analyzer. Studies conducted to see the stability of the samples using a hematology analyzer with impedance technology. Tests performed on whole blood samples collected from 12 ostensibly healthy individuals, immediately after collection (fresh sample, <1hour) and 2h, 4h, 6h, 8h, 24h, 48h afterward. The samples stored at room temperature (20-240C) and 2-60C. There are no significant differences after 48 h under different storage conditions for Hb, Hct, RBC, PLT count, except for WBC count that has a significant difference at temperature 2-60C. CV for Hb, Hct, RBC, PLT, WBC count is less than 5% at room temperature. WBC and PLT count have a CV of more than 5% at 2-60 C. Sample for Hb, Hct, RBC was found to be stable up to 48 h at room temperature and 2-60C. PLT and WBC count were stable for 48 h if stored at room temperature.